Renal oncocytoma with vacuolated cells and giant mitochondria: Report of a rare tumor and review of the literature - Ashmi Patel; Jaden Aland; Haneen Salah; Luan D. Truong; David W. Goldfarb; Ziad M. El-Zaatari (Elsevier, 2023)
Reports of renal oncocytoma with intracytoplasmic vacuoles are exceedingly rare. In addition to 5 prior reports, we present a novel case of renal oncocytoma with cytoplasmic vacuolation. A 69-year-old male patient underwent partial nephrectomy to remove the 3.8 cm tumor. Tumor cells showed typical morphologic and immunohistochemical features of renal oncocytoma, with the additional feature of diffuse, oval-round cytoplasmic vacuoles containing pale amphophilic material. Distinct eosinophilic cytoplasmic inclusions were also present, which were shown to be giant mitochondria on ultrastructural examination. Cytoplasmic vacuolation has been described in other renal tumors, namely succinate dehydrogenase deficient renal cell carcinoma and eosinophilic vacuolated tumor, both of which were ruled out in the current case. Our case is the first to confirm the presence of giant mitochondria in a vacuolated renal oncocytoma, and the second to associate mitochondria as the origin of these vacuoles. Future identification of additional cases would shed more insight on the etiology and pathobiological significance of this rare tumor morphology.